2006
DOI: 10.1021/jf061734j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Germination and Thermal Treatments on Folates in Rye

Abstract: Effects of germination conditions and thermal processes on folate contents of rye were investigated. Total folate contents were determined microbiologically with Lactobacillus rhamnosus (ATCC 7469) as the growth indicator organism, and individual folates were determined by high-performance liquid chromatography after affinity chromatographic purification. Germination increased the folate content by 1.7-3.8-fold, depending on germination temperature, with a maximum content of 250 micro g/100 g dry matter. Hypoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 26 publications
6
36
0
Order By: Relevance
“…A maximum 3.6-fold folate concentration in the sprouted wheat and 1.7-3.8-fold in sprouted rye were obtained on day 5 of germination [8,9]. The total folate concentration remained above the baseline after subsequent heat treatment of sprouted rye [8].…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…A maximum 3.6-fold folate concentration in the sprouted wheat and 1.7-3.8-fold in sprouted rye were obtained on day 5 of germination [8,9]. The total folate concentration remained above the baseline after subsequent heat treatment of sprouted rye [8].…”
mentioning
confidence: 89%
“…A maximum 3.6-fold folate concentration in the sprouted wheat and 1.7-3.8-fold in sprouted rye were obtained on day 5 of germination [8,9]. The total folate concentration remained above the baseline after subsequent heat treatment of sprouted rye [8]. However, the data were presented on substantial reduction in vitamin B 1 content after 3 days of germination in corn and oats [6].…”
mentioning
confidence: 90%
“…The B-vitamin folate is essential for cell replication and occurs naturally in cereal-based foods. Germinated cereals are reported to be an even richer folate source (Kariluoto et al, 2006;Koehler et al, 2007;Hefni and Witthöft, 2011), because of de novo synthesis of folate in the growing seedling (Jabrin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…According to EU Regulation (EC) No. 1924No. /2006 it is possible to claim that sprouted grains are a "source of fibers" or are "rich in fibers" depending on their fiber content.…”
Section: Sprouted Grains As Whole Grainsmentioning
confidence: 99%
“…However, when looking at the existing scientific evidence, the results are mixed (28), and the published studies are difficult to compare because the types and varieties of grains, soaking conditions (water quality), germination conditions (duration and temperature), and measurement methods differ from one study to another. Several studies (8,9,13,14,17,(19)(20)(21)(22)27,31,(36)(37)(38)(39) reported an increase in the levels of some vitamins and minerals with sprouting, while other studies reported no impact or even reduced levels of some vitamins and minerals (2,8,9,17,19,30,31,35). A summary of the results observed for two vitamins, B 9 and E, across various studies is provided in Table I.…”
Section: Nutrient Content Of Sprouted Grainsmentioning
confidence: 99%